2017
DOI: 10.1097/mbp.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and left ventricular mass index in healthy adolescents

Abstract: Primary hypertension among children and adolescents is increasing in prevalence and has been associated with the sequela of left ventricular hypertrophy (LVH), defined by increased left ventricular mass index (LVMI). The association between high blood pressure (BP) and LVMI in an otherwise healthy pediatric population is not well understood. We evaluated the relationship between measures of BP and LVMI in a group of healthy adolescents. We conducted a retrospective review of 55 high school athletes who partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…El interés que manifiestan en la actualidad investigadores y clínicos en el tema de la HTA en niños y adolescentes se debe a que la evidencia muestra que la PA elevada es mucho más prevalente de lo que se suponía (1,2) . Además, estudios han demostrado que la PA alterada en estas edades se traducen en HTA en la etapa adulta, así como cambios en órganos diana como: deterioro cognitivo, hipertrofia ventricular izquierda y marcadores subclínicos de enfermedad cardiovascular, por ejemplo, aumento del grosor de la íntima medio carotídea y síndrome metabólico a muy temprana edad (4) . Por lo que es importancia destacar la vigilancia de este fenómeno no solo a nivel clínico epidemiológico, considerando la prevención como herramienta primordial.…”
Section: Introductionunclassified
“…El interés que manifiestan en la actualidad investigadores y clínicos en el tema de la HTA en niños y adolescentes se debe a que la evidencia muestra que la PA elevada es mucho más prevalente de lo que se suponía (1,2) . Además, estudios han demostrado que la PA alterada en estas edades se traducen en HTA en la etapa adulta, así como cambios en órganos diana como: deterioro cognitivo, hipertrofia ventricular izquierda y marcadores subclínicos de enfermedad cardiovascular, por ejemplo, aumento del grosor de la íntima medio carotídea y síndrome metabólico a muy temprana edad (4) . Por lo que es importancia destacar la vigilancia de este fenómeno no solo a nivel clínico epidemiológico, considerando la prevención como herramienta primordial.…”
Section: Introductionunclassified
“…1 Rates of elevated blood pressure (BP) in children may be underestimated on the basis of current practices and guidelines because of the increasing prevalence of obesity in young people. Hypertension in youth is a condition that has been associated with target-organ changes, such as impaired cognition, 2 left ventricular hypertrophy (LVH), 3 and subclinical markers of cardiovascular disease (CVD), for example, increased carotid intima thickness. 4 Observational studies in youth have demonstrated an association between BP values .90th percentile and alterations in cardiac and vascular structure.…”
mentioning
confidence: 99%